2012
DOI: 10.1007/s11126-012-9248-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of High Doses of Quetiapine in Bipolar Disorder Episodes are not Linked to High Activity of Cytochrome P4503A4 and/or Cytochrome P4502D6

Abstract: The use of quetiapine for treatment of bipolar disorders at a higher dosage than the licensed range is not unusual in clinical practice. Quetiapine is predominantly metabolised by cytochrome P450 3A4 (CYP3A4) and to a lesser extent by CYP2D6. The large interindividual variability of those isozyme activities could contribute to the variability observed in quetiapine dosage. The aim of the present study is to evaluate if the use of high dosages of quetiapine in some patients, as compared to patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Although a dose increase to 500 mg twice daily would be sufficient to ensure 30–50% of subjects attained the upper therapeutic window of 100 ng/ml (Table ), a dose increase to 700 mg twice daily was identified as satisfying the requirement to attain both the 50 and 100 ng/ml lower windows (Figure ), with attainment of >95 and >62% of subjects, respectively. While trials have suggested an upper dose of 800 mg/day, higher doses of between 800 and 2000 mg/day have been reported to be tolerated in acute and maintenance therapy. Further, sparse case reports are available of significantly higher overdoses of least 20–24 g being ingested with little acute effects …”
Section: Discussionmentioning
confidence: 99%
“…Although a dose increase to 500 mg twice daily would be sufficient to ensure 30–50% of subjects attained the upper therapeutic window of 100 ng/ml (Table ), a dose increase to 700 mg twice daily was identified as satisfying the requirement to attain both the 50 and 100 ng/ml lower windows (Figure ), with attainment of >95 and >62% of subjects, respectively. While trials have suggested an upper dose of 800 mg/day, higher doses of between 800 and 2000 mg/day have been reported to be tolerated in acute and maintenance therapy. Further, sparse case reports are available of significantly higher overdoses of least 20–24 g being ingested with little acute effects …”
Section: Discussionmentioning
confidence: 99%